1992
DOI: 10.1016/0014-5793(92)80674-6
|View full text |Cite
|
Sign up to set email alerts
|

Parathyroid hormone‐related peptide can regulate the growth of human lung cancer cells, and may form part of an autocrine TGF‐α loop

Abstract: Parathyroid hormone-related peptide (PTHrP) and transforming growth factor-2 (TGF-o) were found to stimulate proliferation 01' human lung cancer cells (BEN-57). TGF-a stimulated PTMrP secretion from these cells. The polyclonal antisera raised against PTi!rP significantly inhibited the growth of BEN-57 cells. and also the proliferation induced by TGF-cc, Treatment of cells ror up to IO days with either a PTHrP reccplor antagonist (PTHrP(7-34)) or PTHrP antiserum significantly inhibited the subseyucnl growth ot'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
1

Year Published

1997
1997
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 26 publications
0
16
1
Order By: Relevance
“…In addition, PTH-rP has been shown to play a role in causing cachexia in tumorbearing mice. 5 Alternatively, several previous studies have demonstrated that PTH-rP is an autocrine growth factor for tumors such as rat Walker 256 carcinoma 27 and BEN human lung carcinoma, 28 both of which are associated with hypercalcemia. More recently, it has been reported that PTH-rP promotes the progression and metastases of rat malignant pituitary tumor 23 and human prostate carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, PTH-rP has been shown to play a role in causing cachexia in tumorbearing mice. 5 Alternatively, several previous studies have demonstrated that PTH-rP is an autocrine growth factor for tumors such as rat Walker 256 carcinoma 27 and BEN human lung carcinoma, 28 both of which are associated with hypercalcemia. More recently, it has been reported that PTH-rP promotes the progression and metastases of rat malignant pituitary tumor 23 and human prostate carcinoma.…”
Section: Discussionmentioning
confidence: 99%
“…Peptide growth factor agonists for the EGFR include epidermal growth factor (EGF), transforming growth factor α (TGFα,) amphiregulin (AREG), heparin-binding EGF-like growth factor (HB-EGF), betacellulin (BTC), epiregulin (EPR) and epigen (EPG) [17]. Consequently, exogenous application of EGF and TGFα activated PTHrP gene expression in many types of epithelial cells [18][19][20][21]. Indeed, autocrine expression of AREG and consequent stimulation of EGFR signaling appears to account for the high levels of PTHrP produced by cultured keratinocytes [14].…”
Section: Introductionmentioning
confidence: 99%
“…PTHrP demonstrates widespread distribution in lung carcinomas, being present in a high percentage of lung tumors (13) of all histological types (4). In addition, PTHrP is an autocrine growth factor for lung cancer cells (5) and protects them from apoptosis (11), characteristics that could contribute to a cancer's capacity for unregulated growth. Furthermore, PTHrP induces expression of metalloproteinases in carcinoma cells and may stimulate angiogenesis in tumors (3,17) These factors are important in providing a carcinoma with the means to develop its blood supply, to invade into adjacent tissues, and to metastasize.…”
mentioning
confidence: 99%